Effect of iron supplementation on psychomotor development of non-anaemic, exclusively or predominantly breastfed infants: a randomised, controlled trial. Issue 11 (24th November 2015) - Chmielewska, Anna; Chmielewski, Grzegorz; Domellöf, Magnus; Lewandowski, Zbigniew; Szajewska, Hania
Abstract : Introduction: Uncertainty exists regarding the effects of iron supplementation during infancy on neurodevelopmental outcomes in the absence of anaemia. The aim of the study is to establish whether psychomotor and mental development is influenced by early iron supplementation in healthy, non-anaemic, exclusively or predominantly breastfed infants. Methods and analysis: Healthy term infants will be recruited. If exclusively or predominantly breast fed (>50% of daily feedings) and not anaemic at 4 months, they will be randomised to receive either iron pyrophosphate (approximately 1 mg/kg) or placebo daily until 9 months of age. The primary outcome measure is neurodevelopment assessed with the Bayley Scales of Infant and Toddler Development (Bayley-III) at 12 months, and repeated at 24 and 36 months of age. Haematological parameters of iron metabolism also will be measured. Ethics and dissemination: The Bioethics Committee of the Medical University of Warsaw approved the study protocol before recruitment started. Study results will be submitted to peer-reviewed journals in the fields of paediatrics and nutrition, and presented at relevant conferences. Trial registration number: NCT02242188.